2015
DOI: 10.15740/has/au/10.4/318-322
|View full text |Cite
|
Sign up to set email alerts
|

Study on knowledge and adoption of green gram production technology by farmers in Chhotaudaipur district of Gujarat

Abstract: SUMMARY :Farmers had average knowledge about improved practices of green gram cultivation in the Chhotaudaipur district of Gujarat. Farmers possessed comparatively more knowledge about high yielding varieties and time of sowing. Minimum knowledge was possessed in plant protection measures and fertilizer application in greengram cultivation and majority of greengram growers were in medium adoption group followed by low and high adoption group. Greengram growers adopted high yielding variety, seed rate and spaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
2
1
1
Order By: Relevance
“…These results are in line with findings of Dhayal and Mehta (2018), Rajbhar et al (2018), Momin et al (2021) and Rajan et al (2021).…”
Section: Srsupporting
confidence: 92%
“…These results are in line with findings of Dhayal and Mehta (2018), Rajbhar et al (2018), Momin et al (2021) and Rajan et al (2021).…”
Section: Srsupporting
confidence: 92%
“…It can be inferred that cent percent of adoption of technologies were found in case of sowing time by both TS 3R and GRG 811 growers. Similar results were reported by Islam et al (2013) [7] , Dhayal and Mehta (2015) [5] and Brunda, (2018) [3] , wherein majority of farmers who adopted the recommended technologies were found to be more with respect to time of sowing. The highest percent of adoption in TS 3R variety cultivators were seed rate and intercultivation.…”
Section: Extent Of Adoption Of Pigeonpea Technologies By Sample Farmerssupporting
confidence: 87%
“…55% had no formal education; 62% had less than 30 years of farming experience; 42% had an annual income below Rs.25,000/-and 35% had an annual income ranging between Rs.25,000-40,000/-.The main crops in the village were paddy, cotton, maize, sorghum, pigeon pea and vegetables. With regard to age, similar results were reported by Dhayal and Mehta [18,19,20] in their studies that majority of the farmers who adopting different crop technologies were found in middle age group.…”
Section: Socio-demographic Characteristics Of Study Respondentssupporting
confidence: 83%